PENGARUH KUALITAS WEBSITE TERHADAP LOYALITAS PELANGGAN ONLINE SHOP MELALUI KEPERCAYAAN (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang Prodi Manajemen Angkatan 2015 - 2018) - Miftakhul Ilham Fauzi; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG)
AbstractThis study aims to analyze the direct influence and indirect influence of the three variables, namely Website Quality, Trust and Loyalty to Online Shop Customers. This type of research is a type of Explanatory Research using a quantitative approach. This research was conducted by distributing questionnaires to Students of the Faculty of Economics and Business UNISMA Management Study Program Force 2015 - 2018 with a total of 93 respondents. The analysis technique used in this study is path analysis. The results of this study indicate that: (1) the quality of the website has a significant effect on trust of 0.868, (2) the quality of the website has a significant effect on loyalty of 0.856, (3) trust has a significant effect on loyalty of 0.858 and (4) the quality of the website towards loyalty through trust by 0,745. Keyword: Website Quality, Trust, Loyalty